Боротьба радянських органів державної безпеки з «антирадянськими елементами»: 1934–1941 рр. - Баран, Володимир Кіндратович; Baran, Volodym (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі розсекречених архівних документів проаналізовано зміст і головні напрями боротьби радянських органів державної безпеки з так званим антирадянським елементом у 1934–1941 рр.The article lays down the analysis of the scope and methods of operation of the Soviet state security bodies in 1934-1941. It describes the technology of political search as the main profile of Stalin’s special services. On the basis of documents of NKVD of the USSR the categories of the so-calltd «anti-Soviet element» are described.
Soviet sTate Security Bodies Struggle Against «Anti-Soviet Element»: 1934–1941
Keywords: органи державної безпеки; НКВС; «антирадянський елемент»; state security bodies; NKVD (People’s Commissariat for Internal Affairs); «anti-Soviet element»